Milk pH, acid base status, and growth in babies. Issue 12 (December 1978) - Berger, H M; Scott, P H; Kenward, C; Scott, P; Wharton, B A
Abstract : Metabolic acidosis is common in babies fed cows' milk-based formulae. Therefore the effects of adding alkaline salts (sodium and potassium citrate) to a demineralised whey formula were studied in vitro and in 26 low birthweight babies fed on the formula or formula plus citrate. The alkali altered the pH and titratable acidity to a value nearer human milk but it increased the buffering capacity to a value further away. This may effect the bacterial flora of the intestine. The babies fed on formula plus citrate did not make greater gains in weight, length, head circumference, skinfold thickness, or midarm muscle circumference, although they had a greater blood base excess. Some of these babies developed a mild metabolic alkalosis and 3 had hyponatraemia despite their increased sodium intakes. These babies also had lower levels of plasma transferrin but showed no differences in urea, albumin, cholesterol, and calcium levels. No baby fed on the demineralised whey formula without added citrate had a base deficit exceeding 5 mmol/l; late metabolic acidosis is less common in babies fed on this formula and the routine addition of alkali can have untoward metabolic effects.